Pelabelan Titik Bimagic Terbalik Super pada Path Related Graphs - Amalia Rusita; Alifah Prameswari Yosi; Titin Martini (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2026)
A graph is a connected, undirected, and simple graph where is a set of vertices and is a set of edges. Graph with vertices and edges is said to admit a reverse vertex bimagic labeling if there exists a bijection such that for each , for two distinct and . Then, reverse vertex bimagic labeling is called super if label of edges are . A graph that admits reverse super vertex bimagic labeling is called reverse super vertex bimagic graph. The concept of reverse super vertex bimagic labeling in graph labeling arises from the existence of graphs that admit a reverse super vertex bimagic labeling but do not admit a reverse super vertex magic labeling. In addition, this concept aims to extend the range of magic constants, which were initially restricted to positive values, to include non-negative values. In this research, we investigated reverse super vertex bimagic labeling of path related graph, there are path graph , brush graph and centipede tree graph .The method used is an explicit construction of a bijective labeling function . The results show that path graph, brush graph and centipede tree graph are reverse super vertex bimagic graphs with the bimagic sums of each being , for path graph, , for brush graph, and for centipede tree graph.